Art and Science: Where Numerology and Mathematics Touch the Lung - S Marsh Tenney (Canadian Respiratory Journal)
Mathematical analysis in the physical seiences has a long history that reveals not only a rich harvest of fundamental insights but also leads to a wonderment at the in trinsically formal beauty in nature. Rigorous analysis or form and function in the biological sciences has been a more recent innovation. but introduction of' the principles of similarity. scaling, fractal geometry, harmony and proportion has hroadened our perspective. The lung provides an apt example to illustrate the usefulness of this kind or thinking.